U.S. history as women's history : new feminist essays - Kerber, Linda K.; Kessler-Harris, Alice; Sklar, Kathryn Kish (Gender & American culture., 1995)
This outstanding collection of fifteen original essays represents innovative work by some of the most influential scholars in the field of women's history. Covering a broad sweep of history from the American Revolution to contemporary times and ranging over the fields of legal, social, political, and cultural history, this book, according to its editors, "intrudes into regions of the American historical narrative from which women have been excluded or in which gender relations were not thought to play a part."